2022
DOI: 10.3390/ijms23073568
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Preimplantation Genetic Testing for Aneuploidy and the Mystery of Genetic Material: A Review Article

Abstract: This review focuses on recent findings in the preimplantation genetic testing (PGT) of embryos. Different preimplantation genetic tests are presented along with different genetic materials and their analysis. Original material concerning preimplantation genetic testing for aneuploidy (PGT-A) was sourced by searching the PubMed and ScienceDirect databases in October and November 2021. The searches comprised keywords such as ‘preimplantation’, ‘cfDNA’; ‘miRNA’, ‘PGT-A’, ‘niPGT-A’, ‘aneuploidy’, ‘mosaicism’, ‘bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…However, there is growing evidence to support that the cfDNA in SCM is not derived solely from these two embryo mechanisms. If that was the case, aneuploid cells would be over-represented in these samples, which is not what have been reported in recent studies, that observed high concordance rates between SCM and TE or ICM (Huang et al, 2019) Recently, it was proposed that part of the cfDNA in culture media could be from extracellular vesicles (EV) and these genetic sources are important non-invasive clues of embryo well-being (Hawke et al, 2021b;Tomic et al, 2022). On the other hand, according to Orvieto et al (2021), 55.5% of euploid blastocysts expel aneuploid debris, suggesting that the primary source of cellfree DNA in culture media is aneuploid blastomere extrusion and/or their fragments as a result of embryo self-correction, therefore, the blastocyst chromosomal diagnosis could be potentially useless (Orvieto et al, 2021).…”
Section: Non-invasive Pgtamentioning
confidence: 94%
“…However, there is growing evidence to support that the cfDNA in SCM is not derived solely from these two embryo mechanisms. If that was the case, aneuploid cells would be over-represented in these samples, which is not what have been reported in recent studies, that observed high concordance rates between SCM and TE or ICM (Huang et al, 2019) Recently, it was proposed that part of the cfDNA in culture media could be from extracellular vesicles (EV) and these genetic sources are important non-invasive clues of embryo well-being (Hawke et al, 2021b;Tomic et al, 2022). On the other hand, according to Orvieto et al (2021), 55.5% of euploid blastocysts expel aneuploid debris, suggesting that the primary source of cellfree DNA in culture media is aneuploid blastomere extrusion and/or their fragments as a result of embryo self-correction, therefore, the blastocyst chromosomal diagnosis could be potentially useless (Orvieto et al, 2021).…”
Section: Non-invasive Pgtamentioning
confidence: 94%
“…Minimally invasive and noninvasive methods either acquire embryo‐associated material without removing any embryonic cell material, or employ extracellular sampling, also without removal of any embryonic cell material. Sampling methods have thus expanded from polar body, blastomere, and trophectoderm (TE) biopsies to include the analysis of cell‐free DNA and extracellular vesicles from embryo culture medium, and analysis of cell‐free DNA from blastocoel fluid (Alizadegan et al, 2022; Chen et al, 2021; Giacomini et al, 2020; Gianaroli et al, 2014; Gombos et al, 2021; Huang et al, 2019; Shamonki et al, 2016; Shi et al, 2022; Tomic et al, 2022). The application of this increasingly complex array of sampling methods has been driven by the desire to deliver higher‐quality genetic information to enable the selection of highest quality embryos for embryo transfer, to overcome complications such as embryo mosaicism, and to maximize live birth rate, while avoiding major causes of miscarriage, particularly aneuploidy (Greco et al, 2020).…”
Section: Expansion Of Sampling Methodsmentioning
confidence: 99%
“…Recently, the discovery of cell-free DNA in SCM prompted the development of non-invasive PGT-A (niPGT-A) [ 19 ]. Although niPGT-A has emerged as a potential alternative to conventional PGT-A for safety and economic reasons, the contamination of maternal cell-free DNA in SCM and the concordance between PGT-A and niPGT-A still need to be determined [ 20 ]. Various biomarkers for the non-invasive assessment of embryo viability and implantation potential have been proposed.…”
Section: Introductionmentioning
confidence: 99%